75.7k views
3 votes
Y+2=−3(x−4) Complete the missing value in the solution to the equation. ( ,-2)

User Duffp
by
6.0k points

2 Answers

2 votes


\bf y+2=-3(x-4)~\hspace{5em}(\stackrel{x}{\phantom{X}},\stackrel{y}{-2})~\hspace{5em} \stackrel{y=-2}{(-2)+2=-3(x-4)} \\\\\\ 0=-3x+12\implies 3x=12\implies \implies x=\cfrac{12}{3}\implies x=4 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill (\stackrel{x}{4},\stackrel{y}{-2})~\hfill

User Jan Swart
by
5.8k points
6 votes

The missing value is 4.

User Jamiebarrow
by
6.2k points